Photoredox-controlled mono- and di-multifluoroarylation of C(sp3)-H bonds with aryl fluorides - Xie, Jin; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2017)
A controllable mono- and di-multifluoroarylation of acyclic and cyclic N-aryl amines with aryl fluorides by photocatalyzed dual C(sp3)−H/C(sp2)−F functionalization has been developed, providing new access to a wide array of valuable α-fluoroarylated amines. In addition, the one-pot consecutive hetero-di-multifluoroarylation of N-aryl pyrrolidines and N,N-dimethylanilines was achieved with high to excellent diastereoselectivity. This new defluorinative C(sp3)−C(sp2) coupling is distinguished by a broad scope, good regioselectivity, and mild conditions as well as gram-scale and late-stage applicability, and thus constitutes a significant advance in the arylation of unactivated C(sp3)−H bonds with aryl fluorides.